The use of habitat interventions to enhance natural pest regulation services in Spanish orange orchards - Mockford, Alice (2022)
To meet the rising demand for food from a growing human population, modern agriculture has focused on intensification by mechanising agricultural processes, converting land to agriculture, removing ecological infrastructure to maximise field sizes, and increasing agrochemical inputs (synthetic fertilisers and plant protection products). This has resulted in habitat loss, environmental pollution, and increased greenhouse gas emissions which has contributed to the accelerated loss of biodiversity and global climate change. In turn, ecological processes have been disrupted, including economically important ecosystem services that underpin food production, such as pest regulation. Interventions which protect and support ecosystem services must be applied to agricultural systems to enable the increasing demand for food to be met sustainably. Wildflower habitats provide resources for natural enemies of crop pests, including carbohydrates (nectar, honeydew, and guttation), protein (pollen and alternative host/prey), and shelter, and can therefore support populations of natural enemies, which spill-over onto adjacent crops, and ultimately enhance pest regulation services. Orange is an economically important fruit crop in Spain, worth €1.24 billion annually. Spanish orange orchards are characterised by a high diversity of native and naturalised natural enemies which successfully regulate many potential citrus pests. However, some pests still avoid successful control. For the delivery of robust Integrated Pest Management programmes, habitat management strategies must therefore be developed for Spanish orange orchards to support natural enemies and their pest regulation services. Replicated blocks established within larger commercial citrus orchards (>300 ha) in Huelva, Andalucía, were used to investigate the effect of a novel wildflower habitat sown in the orchard alleyways under different management strategies on natural enemy abundance and the delivery of pest regulation services in Spanish Navel orange orchards. Two management treatments were applied to the wildflower habitats: I) a standard management treatment, whereby the wildflower habitats were managed by cutting once annually in February, and II) an active management treatment, for which the wildflower habitat received two additional cuts each year, once in May and again in July, to coincide with predicted incidence of a key pest of citrus, Aonidiella aurantii Maskell (Hemiptera: Diaspididae). These management treatments were compared against control alleyways whereby alleyways were managed conventionally by cutting the naturally occurring vegetation four to five times annually. For the first time, it was demonstrated that species-rich wildflower strips can be established successfully in Spanish orange orchards, doubling plant richness in the alleyways, and supporting distinct plant communities compared to conventionally managed alleyways. In turn, this provided resources to support natural enemies. Carbohydrate feeding in parasitoids, a prerequisite for optimised host foraging, was increased and natural enemy abundance on orange trees was boosted in association with the standard wildflower treatment, without increasing the relative abundance of hyperparasitoids. This enhanced pest regulations services during a period of the year critical for the control of several economically important pest species (June-July). However, actively managing the wildflower alleyways by cutting resulted in a reduced abundance of the sown species during the three-year study. Rather than encouraging spill-over, the increased disturbance was associated with reduced abundance of natural enemies on the crop, decreased incidence of parasitoids recently fed on carbohydrate, and diminished pest regulation services. This study has shown that wildflower habitats under standard management can enhance the delivery of pest regulations services in commercial orange orchards. To optimise this service, wildflower habitats should therefore be managed by cutting just once annually, allowing alleyways to grow throughout the rest of the year. The adoption of this strategy could allow growers to reduce the use of plant protection products and provide a more environmentally and economically sustainable approach to pest regulation in Spanish orange orchards.